2021
DOI: 10.3906/sag-2102-24
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-21: a potential biomarker for diagnosis and predicting prognosis in COVID-19 patients

Abstract: Background/aim: COVID-19 patients have a wide spectrum of disease severity. Several biomarkers were evaluated as predictors for progression towards severe disease. IL-21 is a member of common γ-chain cytokine family and creates some specific effects during programming and maintenance of antiviral immunity. We aimed to assess IL-21 as a biomarker for diagnosis and outcome prediction in patients hospitalized with COVID-19. Materials and methods:Patients with a preliminary diagnosis of COVID-19 and pneumonia othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Recent studies on serum levels of IL-17 [33] , [34] and IL-21 [35] represented their effect as an amplifier and boosting factor for the COVID-19 progression. We have seen that in COVID-19 individuals the level of these mentioned cytokines raised above the control patients’ level which showed that miR-155 indirectly control them by affecting SOCS-1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on serum levels of IL-17 [33] , [34] and IL-21 [35] represented their effect as an amplifier and boosting factor for the COVID-19 progression. We have seen that in COVID-19 individuals the level of these mentioned cytokines raised above the control patients’ level which showed that miR-155 indirectly control them by affecting SOCS-1.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, it has been reported that during COVID-19 infection, SARS-CoV-2-specific TFH decreases the CCR6 expression favoring homing to the mucosal airway [ 29 ], thus reducing their frequency in blood. One limitation of this study was not performing IL-21 analysis in serum samples; it has been shown that IL-21 promotes B and plasma cell development [ 30 ], as well as stimulates the differentiation of TFH. It is necessary to consider analyzing the IL-21 in serum samples in an intracellular manner after in vitro stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that high serum levels of IL-21, but not IL-6, are a predictive indicator for poor prognosis in COVID-19 patients. 22 The high serum concentration of IL-21 could also be due to other contributing cell populations, such as central memory T cells and Th17 cells. 23,24 Similar to our findings, the significance of circulating IL-1β in severity has been established by other studies, targeting it as a therapeutic agent.…”
Section: Cytokine Profiling Suggests a Pro-inflammatory Environment I...mentioning
confidence: 99%